От поэтики А. Потебни к теории интертекстуальности - Дзык, Роман (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The article analyses the relation of O. Potebnya’s concepts to the theory of intertextuality. The attention to the peculiar interpretation of the notion of “poetic language” by the Russian formalists and their successors, as well as to the development of the dialogical nature of the word and the text, according to M. Bakhtin, reconstructs the genetic connection between the above theoretical systems. The consonance of Potebnya’s ideas with the modern theory is explained by typological convergence. At the same time, the article discusses the productive perspective of the appeal of Potebnya’s ideas in the light of the new literary methodology.
From O. Potebnya's Poetics to the Theory of Intertextuality
Keywords: poetyka; intertekstualność; Potebnia Ołeksandr